EFEKTIVITAS PELAYANAN PENGINTEGRASIAN INFORMASI MELALUI PUSAT INFORMASI PUBLIK DI DINAS KOMUNIKASI, INFORMATIKA, STATISTIK, DAN PERSANDIAN KOTA SEMARANG - Nur Vita Rahmawati; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
This study aims to describe the effectiveness of information integration services through the Public Information Center (PIP) in the Office of Communication, Informatics, Statistics and Coding of Semarang City. In reality, the implementation of information integration in PIP is still a problem that exact time of fulfilling the request for information that is more than 10 days maximum conditions. The method used in this study is descriptive qualitative using taxonomic analysis with examine the element that achievement of objectives said to be successfully supported by organizational factors in the form of a clear division of labor according to the Standard Operating Procedure (SOP) in achieving its goal as realization of information centralization, but there are factors that inhibits the implementation is the lack of technological capabilities experienced by employees in the integration of information. Second, integration is influenced by conducive environmental factors that support the integration of information, but labor factors inhibits the integration of information because there are rolling employees that cause new employees to be required to understand their tasks from the beginning. Third, adaptation is supported by organizational factors in the form of a division of labor in accordance with the SOP so as to minimize errors when the adaptation process is carried out, but the worker factor inhibits the implementation of adaptation due to lack of understanding of the device regarding information integration. Recommendations for other researchers are expected to examine the institutional form and position of PIP.